(untitled) (The Review of Diabetic Studies, 2025)
This study aims to examine the relationship between work stress and burnout among paramedics working for the Saudi Red Crescent Authority. This is due to the nature of their profession, which requires constant response to emergencies, critical injuries, and traumatic situations, making them more susceptible to occupational stress and burnout. The study used the descriptive analytical approach due to its suitability to the nature of the subject. Data were collected from a sample of (200) paramedics working in the field through a questionnaire consisting of (12) items designed to measure the level of work stress and symptoms of burnout, using a three-point Likert scale (agree - neutral - disagree). Data were analyzed using descriptive and inferential statistical methods such as means, standard deviations, Pearson correlation coefficient, independent samples t-test, and one-way analysis of variance (ANOVA). The results showed high levels of work stress among sample members, particularly in items related to long working hours, frequent critical incidents, and poor psychological support in the workplace. There was also a strong positive correlation (r = 0.82, p < 0.01) between work stress and burnout, indicating that increased stress leads to higher levels of emotional exhaustion and lower professional motivation. The results showed statistically significant differences according to years of experience, in favor of those with average experience, while no differences were found between males and females. The study found that work-related stress is a key predictor of burnout and recommended strengthening psychological support programs, work-related stress management, and psychological resilience training for paramedics.